PENERAPAN METODE RECIPROCAL TEACHING DALAM PEMBELAJARAN BAHASA ARAB UNTUK MENINGKATKAN MAHARAH AL-QIRA’AH DI SMP ISLAM AL-BAYYINAH MAKASSAR - Zainal, Abdul Qahar; Halifah, Hamidatul; Hafid, Wahyudin; Syahrul, Muhammad; Abna, Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the Reciprocal Teaching method in Arabic language learning and analyze its improvement in the maharah al-qira'ah of class VIII B students of Al-Bayyinah Islamic Middle School, Makassar. This study is motivated by the low reading comprehension ability of students in Arabic language subjects, which is characterized by low ability to understand vocabulary, find main ideas, and summarize the content of the reading. Therefore, a learning method is needed that can increase student active involvement in understanding Arabic reading texts. This study uses a Classroom Action Research (CAR) type with a mixed method approach, namely qualitative and quantitative. The study was carried out in two cycles, each of which includes the planning stage, action implementation, observation, and reflection. The research subjects were 33 class VIII B students of Al-Bayyinah Islamic Middle School, Makassar. Data collection techniques used include observation, tests (pretest and posttest), interviews, and documentation. Data were analyzed using qualitative and quantitative descriptive analysis techniques to determine the process and results of improving students' reading skills. The results of the study showed that the application of the Reciprocal Teaching method which includes the stages of predicting, questioning, clarifying, and summarizing was able to improve students' maharah al-qira'ah. This improvement was seen from the average score of students which increased from 69.39 in the Cycle I pretest to 86.51 in the Cycle I posttest, and increased again to 93.48 in the Cycle II posttest. The percentage of learning completeness also increased from 39.39% in the Cycle I pretest to 96.96% in the Cycle II posttest. In addition, the results of observations and interviews showed an increase in student activity, participation, cooperation, and self-confidence during the learning process. Thus, the Reciprocal Teaching method is effective in improving the maharah al-qira'ah of class VIII B students of SMP Islam Al-Bayyinah Makassar.